Development and application of a RAA-CRISPR/Cas12a-based detection system for the pseudorabies virus gE gene - Song, Chunlian; Wei, Jiajia; Du, Song; Sun, Yalong; Guan, Chen; Li, Jianqin; Wei, Qianfei; Zhang, Xue; Shen, Hong; Shu, Xianghua (Frontiers in Microbiology, 2025)
The development of field-deployable diagnostic tools for pseudorabies virus (PRV) surveillance remains challenging due to the technical limitations of conventional detection methods, particularly their reliance on sophisticated equipment and inadequate sensitivity for gE gene identification in resource-limited settings. To address these critical needs, we established a novel nucleic acid detection platform that synergistically integrates recombinase-aided amplification (RAA) with CRISPR-Cas12a technology. Through systematic optimization of four CRISPR RNAs (crRNAs) and corresponding primer sets targeting conserved regions of the PRV gE gene, validated by fluorescence quantification and electrophoretic analysis, we developed a rapid detection system capable of achieving 10 copies/μL sensitivity within 45 min under isothermal conditions (37 °C). Clinical validation demonstrated complete diagnostic concordance with standard PCR methods, successfully identifying all 11 positive specimens from 30 clinical samples. The platform’s technical innovation lies in its sequential reaction activation mechanism that enables single-tube operation, effectively eliminating aerosol contamination risks while maintaining reaction efficiency. Detection outcomes can be interpreted through dual modalities—real-time fluorescence monitoring for quantitative analysis and lateral flow strips for visual readouts significantly enhancing field applicability. Notably, this system exhibits a 1,000-fold sensitivity improvement compared to conventional PCR, establishing itself as a robust solution for point-of-care PRV monitoring with particular utility in veterinary settings lacking advanced laboratory infrastructure.